2011
DOI: 10.1364/josaa.28.000576
|View full text |Cite
|
Sign up to set email alerts
|

Full wave optical profilometry

Abstract: We show that tomographic diffractive microscopy can be used for profilometry applications with high transverse resolution. We present an iterative reconstruction procedure, based on a rigorous wave scattering model, that permits us to retrieve the profile of rough metallic interfaces from the complex scattered field. The transversal resolution is subwavelength, and can even fall below the classical resolution limit if the profile is rough enough for multiple interactions to occur. Large profiles, with tens of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…A normal height distribution and a Gaussian height spectrum are given to the roughness. With a slope root mean square that corresponds to an angle of 40°, this surface is far too rough to be inverted under the Fraunhofer approximation [12]. The profile is 60 μm long and sampled with 4096 points to compute the scattered field, which corresponds to data.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A normal height distribution and a Gaussian height spectrum are given to the roughness. With a slope root mean square that corresponds to an angle of 40°, this surface is far too rough to be inverted under the Fraunhofer approximation [12]. The profile is 60 μm long and sampled with 4096 points to compute the scattered field, which corresponds to data.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…A preliminary study of the applicability of ODTM to profilometry in the resonance domain has been presented in a previous paper [12]. The importance of using a rigorous method for calculating the scattered field has been stressed, and it has been shown that ODTM can be applied when high lateral resolutions are required.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, care should be taken if multiple reflections occur, as for example for deep metallic samples. The reconstruction methods used here are no longer valid and a more complex scheme should be used to include the effect of multiple scattering, such as iterative reconstruction procedures based on rigorous wave diffraction [41]. Polarization effects are also taken into account by such approaches, which helps distinguish structures below the classical limit of resolution.…”
Section: Discussionmentioning
confidence: 99%
“…This method was efficiently implemented in inverse scattering schemes for two-dimensional [6,16,17] and three-dimensional [18] scattering. However, one requisite of the method is that the incident field is a tapered wave, usually a gaussian beam.…”
Section: Introductionmentioning
confidence: 99%